Uji Organoleptik Kombucha yang terbuat dari beberapa jenis teh dan waktu fermentasi berbeda - Azrini Khaerah; Ardianto Ardianto (BIOEDUSCIENCE, 2023)
Background: This research aims to find the best mixture of kombucha that can accept by the community in BTN Pa’jukukang, Bantaeng district. Kombucha is a fermented beverage made from tea and sugar mixed with the kombucha culture. A kombucha culture is a mixture of bacteria and yeast designated as SCOBY in this work. Methods: In this research, kombucha was made from 4 various teas, i.e., black tea, green tea, oolong tea, and white tea.  Each tea was fermented for 7 and 14 days. The kombucha tea samples were subjected to an organoleptic test based on the consumer's acceptance level. The organoleptic test data were analyzed using the hedonic and score test. Results: The test result showed that respondents preferred to choose the color, the smell, and the taste of the black kombucha tea which was fermented for 7 days. Conclusions: Furthermore, the observation of the physical characteristics of the tea showed that the longer the fermentation time, the more acidic the kombucha. This acidic kombucha resulted from the decreasing sugar level during the fermentation process due to the activity of bacteria and khamir in the SCOBY.